Simulation and test of a V-shaped seed-guiding surface and concave pit furrow opener for seed displacement restriction: Verification on seeding uniformity and post-soil-contact seed motion limitation - Guoqiang Dun; Yang He; Xinxin Ji; Chunyu Ma; Xinming Li; Luhan Wang (PLoS ONE, 2025)
In plot breeding tests, sowing uniformity directly impacts the accuracy of crop genetic improvement trials. Existing furrow openers often cause spacing fluctuations and lateral seed drift due to structural limitations. To address this, a sharp-angle roller furrow opener with independently rotatable V-shaped ball rollers was innovatively designed based on traditional sharp-angle flat-bottom openers, meeting soybean sowing agronomic requirements. The V-shaped ball rollers form V-grooves and spherical pit rows at the furrow bottom through rolling, with ridge-like structures between pits effectively limiting seed longitudinal displacement and rolling jumps upon soil contact, thus improving sowing uniformity. Performance verification was conducted via discrete element simulation and soil trench testing: An EDEM-based soybean seed-soil-opener interaction model was built, using spacing fluctuation coefficients, lateral offset dispersion, and average lateral offset as indexes to compare the new opener with sharp-angle sharp-bottom and flat-bottom openers. Three opener prototypes were 3D-printed and tested on a self-made soil trench bench. Both simulation and bench test results showed that under identical conditions, the new opener significantly reduced spacing fluctuations and lateral offsets, outperforming traditional designs in sowing uniformity and enhancing breeding trial reliability. This study constructs a sustainable agricultural furrow opener design framework through structural innovation and dual experimental validation, integrating mechanical performance optimization with resource-environmental benefits, and provides a new technological pathway for clean production concepts in agricultural equipment.